AGGLOMERATION OF NANOPARTICLES WITH IONIC BONDING - Azimov J. T. (Web of Journals Publishing, 2024)
This work allows us to discuss situations how the form and radius of the ion of particles affect the magnitude of surface charges.
Keywords: Agglomeration of nanoparticles, surface, band gap, ionic bond.